Assessment of catheter-manometer systems used for invasive blood pressure measurement - Heimann, P A (Division of Biomedical Engineering, 2018)
Direct measurement of blood pressure using a fluid-filled catheter and an electromechanical transducer is widely accepted in clinical practice. However, errors associated with the measurement are often not appreciated and these catheter-manometer systems are frequently unable to accurately reproduce applied pressures. To assess the accuracy of catheter-manometer systems used for invasive arterial blood pressure measurements, in vitro and in vivo evaluations were performed. The frequency response (described in terms of damped natural frequency and damping factor) for a variety of cannulae, pressure tubing and stopcocks (and combinations thereof) and their dependence on various parameters (catheter length, lumen diameter, fluid temperature and catheter material) were measured using an hydraulic pressure generator. The design and construction details of the pressure generator are presented. It was found that the damped natural frequency of the catheter-manometer system is directly proportional to lumen diameter of the pressure tubing/catheter. Furthermore, damping factor is inversely related to the damped natural frequency and stiffer catheter material (for identical radius ratios) results in higher damped natural frequency. Catheter length is inversely related to damped natural frequency and the resonant frequency decreases for an increase in fluid operating temperature. It was established that all catheter-manometer systems tested were under-damped (0.15 < β < 0.37) and that the damped natural frequency ranged from 10.5 Hz for 1500 mm to 27.0 Hz for pressure tubing of 300 mm in length. Furthermore, catheter-manometer systems which had pressure tubing in excess of 300 mm in length did not comply with the bandwidth requirements for accurate dynamic blood pressure measurement. For the in vivo assessment of the catheter-manometer system, the blood pressure waveform was analysed in the time and frequency domains. It was established that in 60 percent of the cases, the systolic pressure peak was higher when measured by a narrow bandwidth catheter-manometer system compared to that measured by a wide bandwidth system. Furthermore, values of dp/dt maximum were lower for wide bandwidth catheter-manometer systems than those measured by narrow bandwidth systems for heart rates above 90 beats per minute. In the frequency domain analysis, artifact was sometimes found to occur at frequencies higher than the bandwidth of the catheter-manometer system. This high frequency artifact was found to distort the blood pressure waveform and resulted in false high dp/dt and peak systolic pressures.